The attention of the adolescents of 9-14 years with disorders of rivalry between companions, incorporated to the sport for all in the community - Yuliens Jiménez-Osorio; Marcos Beltrán-Fernández (Universidad de Guantánamo, 2012)
This research presents a system of physical, recreational and educational. Aims to coordinate preventive actions from the community context to improve the performance of the professionals of Physical Culture, this structure in phases for implementation. The novelty lies in exploiting the potential lies in the educational and recreational physical activity for the attention to teens from 9 to 14 years with rivalry disorders. The results of the assessment of the feasibility of the proposal from specialist consultations are satisfactory and it is feasible to implement in social practice.